Arab Republic of Egypt : Gender assessment 2010 - World Bank (World Bank, 2012)
The objective of this policy note is to examine the gender dimension of the Egyptian labor market, with a focus on identifying the scope for policies to improve female labor force participation. An update to the Egypt gender assessment report of 2003, it is envisioned as a contribution to programmatic work on gender and inclusion in Egypt, helping build evidence which can inform policy aimed at improving the participation and retention of women in the labor force. Analytical and investigative in nature, it is the hope that this note will motivate discussion and debate among stakeholders in the country. The questions to be addressed in the note are also relevant for policy discussions and Bank operations in other countries, especially those in the Middle East North Africa (MENA) region where females face similar challenges to labor force participation. Besides laying out the underlying correlates of gender gaps in these areas, the report recommended a comprehensive list of 'strategic interventions' by sector for the government and other development actors, in areas such as investment in women's education, the re-examination of certain discriminatory provisions in the country's legal system, and the promotion of cultural norms that value women as equal partners to men. In the sphere of women's economic opportunities, the report pinpointed vulnerabilities such as high unemployment rates (particularly among the more educated), and a disproportionate dependence on an already shrinking public sector. Highlighting the need for creating productive and sustainable jobs for women in the private sector, the report suggested initiatives such as increasing women's access to training, technology, land, credit and information.